PENERAPAN MODEL INQUIRY LEARNING DENGAN PENDEKATAN CRT DAN GAYA BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V - Ayssyiyah Sintha Balqis; Badarudin; Wiwin Dwi Mulyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The cognitive learning outcomes in science and social studies subjects of students in grade V are low. This study aims to improve the cognitive learning outcomes of students in science and social studies subjects through the application of the Inquiry Learning model with the CRT approach and adjustments to the learning styles of grade V students. This study uses the Classroom Action Research design of the Kemmis and MCTaggart models consisting of two cycles. The subjects of this study were 26 grade V students. Data collection techniques used non-test techniques (observation sheets); and test techniques (evaluation questions). Data analysis techniques with quantitative descriptive. The results of this study indicate: Increased student activity in cycle I by 75% with good criteria to 91.66% with very good criteria; Increased social studies learning outcomes of grade V students with an average of 75 (completeness 80.76%) in cycle I increasing to 95 (completeness 96.15%) in cycle II. The conclusion of this study is that the application of the Inquiry Learning model with the CRT approach and accommodating learning styles has proven effective in improving the cognitive learning outcomes of grade V students.